Undesirable British East African Asians. Nationality, Statelessness, and Refugeehood after Empire. Issue 1 (4th May 2022) - Cosemans, Sara
ABSTRACT: In 1972, upon expulsion from Uganda by Idi Amin, diasporic Asians, who had settled in East Africa during colonial times, underwent a second stage of global dispersal. Many of them managed to resettle in the United Kingdom, despite anti-immigrant sentiments and increasingly restrictive immigration legislation. Other large groups arrived in India and Canada. One group, however, got scattered around the globe: the approximately 10, 000 'Asians of undetermined origin', who were resettled as refugees under auspices of the United Nations High Commissioner for Refugees. This article investigates how and why this group of stateless Asians became refugees and candidates for international resettlement. It argues that all British policy makers sought to use the international community to shoulder part of the burden of winding up empire, while trying to avoid convictions for breaching newly emerging legally binding international human rights obligations. The Ugandan Asian crisis fits within the history of the creation of modern British immigration control law that took shape from 1962 onwards. This article proposes to decentralise the geographical frame beyond the UK to include developments in Kenya, Uganda, and India, where East African Asians likewise became 'undesirables'.